2015
DOI: 10.17221/8388-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Canine mammary anaplastic carcinoma with concurrent aorto-iliac thrombosis in a dog: a case report

Abstract: An 11-year-old, 6.75 kg, spayed female Maltese dog was referred for evaluation of a recurrent mammary gland tumour (MGT) after recent lumpectomies. We performed a regional mastectomy, and the mammary gland tumour was diagnosed as a mammary anaplastic carcinoma. On the 11 th postoperative day, the dog presented with a one-day history of lethargy and left hind limb weakness. Increased D-dimer level and two-dimensional and Doppler ultrasonography revealed a unilateral aorto-iliac thrombus. Although prompt thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
1
4
0
3
Order By: Relevance
“…On the other hand, similar results were reported for percentage of ER expression in benign cancerous tissues, which varied from 49 to 100 [2,23,24,26,28]. Surprisingly, Kim et al, 2015 have shown the ER and PR are decreased in malignant canine mammary tumors [3]. Some investigations indicated that the expression of progesterone and estrogen receptors is associated with tumor size and malignancy grade.…”
Section: Fig (5) Plot Of Logarithmic Fold Change Expression Of Er-αmentioning
confidence: 53%
See 1 more Smart Citation
“…On the other hand, similar results were reported for percentage of ER expression in benign cancerous tissues, which varied from 49 to 100 [2,23,24,26,28]. Surprisingly, Kim et al, 2015 have shown the ER and PR are decreased in malignant canine mammary tumors [3]. Some investigations indicated that the expression of progesterone and estrogen receptors is associated with tumor size and malignancy grade.…”
Section: Fig (5) Plot Of Logarithmic Fold Change Expression Of Er-αmentioning
confidence: 53%
“…About 52% of all tumors correspond to mammary neoplasia, which is repeatedly reported among dogs and is the most common malignant neoplasia among bitches [1,2]. Malignant tumors can be found in roughly 50% of mammary tumors in canids [2][3][4]. Malignant tumors are hormone-dependent neoplasms and might reappear after surgical removal or spread to other organs such as liver, lymph nodes, and lungs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, studies demonstrate the higher risk of clot abnormalities when associated to progression of mammary carcinomas [8]. Studies in veterinary medicine demonstrates that neoplasia were a common concurrent condition associated to thrombosis, and in dogs with distant metastasis had significantly higher fibrinogen and D-dimer concentrations compared to dogs with local disease [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Meme tümörleri dişi köpeklerde sıklıkla teşhis edilmekte 1,6,10 , erkek köpeklerde ise daha nadir olarak gözlenmektedir 1,3,8,12 . Köpeklerde meme tümörlerine daha çok 8-12 yaş aralığında (ortalama 5 yaşından büyüklerde) rastlanmaktadır 1,3 .…”
Section: Introductionunclassified
“…Anaplastik karsinomalar en malign karaktere sahip olan epitel kökenli tümörlerdir. Ade-nokarsinoma, solid karsinoma, skuamoz hücreli karsinoma ya da musinoz karsinoma gibi tümörlerden farklı olarak, tümörün hangi hücreden köken aldığı tam olarak belirlenemez 1,6,9 . Anaplastik karsinomalar köpeklerde diffuz ve invaziv karakterde olup, özellikle bölgesel lenf nodüllerine ve akciğerlere metastaz yapma eğilimindedir 1,[4][5][6]9,10 .…”
Section: Introductionunclassified